Results of a sociological survey of parents of children with mental disabilities on the social effect of the project «Inclusive sports for all» of the special Olympics Russia - Burtseva E.V.; Parfenova L.A.; Rakova M.S. (Theory and Practice of Physical Culture, 2025)
Purpose of the study: to identify the social effects of the project "Inclusive Sports for All", implemented by Special Olympics Russia, based on the results of a sociological survey of parents. Methodology and organization of the research: The study involved a sociological survey of the project’s key stakeholders—parents (743 respondents) and guardians (100 respondents) of athletes with intellectual disabilities from the Ivanovo, Kostroma, and Sverdlovsk regions, the Republic of Tatarstan, and Moscow. While the research did not focus on assessing changes in children’s physical condition, its primary objective was to evaluate parents’ perceptions of the project’s impact. Research results and conclusions: Participation in the Inclusive Sports for All program significantly contributed to children’s development across three key dimensions: physical, personal, and social. Based on the findings, we propose the following measures to enhance the inclusive sports model: Developing a communication strategy for parents—creating and disseminating key messages that explain the purpose and social benefits of inclusive sports participation. Strengthening support systems for coaches—introducing specialized training and resources for professionals working with children with intellectual disabilities. Implementing personalized approaches—incorporating individual-oriented methods to better meet the needs of all participants in inclusive sports programs.